Epidemiology of school injuries in Malaysia - Junainah Sabirin (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2002)
The objective is to study the characteristics of school injuries in terms of age, sex, ethnicity., specific location, time of injury, body parts involved, mechanisms of injury, circumstances and outcome and to identify the physical and mechanical factors involved in injury. This is a descriptive study conducted over a period of three months from 1 June 1996 to 31 August 1996 with the exception of Sarawak, which collected data from 1 August to 31 October 1996. Morbidity and mortality data involving injuries occurring at schools were collected from all patients who sought treatment at government hospitals and clinics in Malaysia with the exception of Perlis. Data were collected using questionnaire and analyzed using Epid Info Programme. There were 1,846 school injuries and of which six were fatal. Majority that is 69.5% of school injuries occurred outdoors. Males had higher incidence of both indoor and outdoor injuries in all age groups. Both outdoor and indoor school injuries peaked during morning break (around 10 a. m ). Falls were the main event leading to injury both indoors (63.1%) and outdoors (43.2%) and in all age groups. Sharp objects or cutting instruments, floor and flooring surfaces were the products commonly identified that could contribute to both indoor and outdoor injuries. Playground surface were identified in 26.3% of outdoor school injuries. Head was the main body parts injured followed by extremities. Majority of injuries were accidental but three out of six deaths were due to homicide. Prevention strategies should be targeted towards prevention of falls.